Accelerated LVAD pump thrombosis in COVID‐19 patient: Case report and mini review. Issue 12 (8th November 2022) - Wadiwala, Ishaq J.; Garg, Pankaj; Alomari, Mohammad; Elawady, Mohamed S.; Alamouti‐Fard, Emad; Raavi, Lekhya; Mateen, Nargis; Khan, Fazal; Hussain, Md Walid Akram; Pham, Si M.; Jacob, Samuel
Abstract: Background: Coronavirus (COVID‐19) infection exposes patients with heart failure specially who are on mechanical support to a higher risk of morbidity and mortality. Aims: To investigate the impact of COVID‐19 infection on left ventricular assist device (LVAD) thrombosis in heart failure patients. Materials & Methods: We searched the medical electronic records, Medline, PubMed and Cochrane databases for; (LVAD) AND (thrombosis)) AND (covid‐19)) AND (heart failure). We divided cases reported into, LVAD thrombosis with COVID‐19 infection and compare them with LVAD thrombosis without COVID‐19 infection. Demographic data, LVAD device, presentation, treatment and outcomes were reviewed in all the LVAD thrombosis patients. Results: In addition to our case, 8 other cases of LVAD thrombosis associated with COVID and 9 cases of LVAD thrombosis without covid infection were found. Patients with Covid infection had worse presentation and outcomes (3 deaths VS. 1 death in non‐covid group). Discussion: In LVAD patients, pump malfunction due to thrombus development in the inflow cannula, device body, or outflow graft can result in hemodynamic instability, hemolysis and other life‐threatening complications. COVID infection significantly increases the risk of mortality in LVAD patient by accelerating the pump thrombosis due to elevated levels of endothelial protein C receptor and thrombomodulin along with procoagulants such as factor VIII, P‐selectin, and von Willebrand factor. Conclusion: Significant morbidity and mortality are attributed to LVAD thrombosis, which are exasperated by prothrombotic conditions created in COVID‐19 infections.